Analisis Kinerja Sistem Informasi Pengiriman Surat Dengan Pendekatan UML Pada Perusahaan Ekspedisi - Mira Permatasari; Nur Nawaningtyas Pusparini (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This study aims to analyze the performance of the mailing system information in an expedition company using the Unified Modeling Language (UML) approach. The mailing information system plays a crucial role in the smooth operation of the expedition company, particularly in managing the dispatch and delivery of letters and documents effectively and efficiently. This research uses a descriptive method with a quantitative approach to illustrate and analyze the extent to which the system's performance meets user needs. Data were collected through a questionnaire distributed to 25 respondents, consisting of 17 females and 8 males, to measure three key aspects of the system: user satisfaction, ease of use, and access speed. The results of the study show that the majority of respondents gave very positive assessments of the system. The easeof use aspect received the highest average score (4.4), followed by access speed (4.28) and satisfaction (4.24). However, there are areas that can still be improved, particularly regarding user satisfaction and system access speed for greater optimization. Overall, the study concludes that the mailing information system in the expedition companys functioning well, but the company needs to continue innovating and improving the system's performance to better meet user expectations.